On elevation of intraocular pressure after intravitreal injections - S. M. Bauer; E. B. Voronkova; K. E. Kotliar (Российский офтальмологический журнал)
The aim of this work is to emphasize the need to take into account several important biomechanical factors (biometrical parameters of patient, s eyes accuracy of tonometers) as well as the design of the procedure when interpreting clinical data of immediate IOP elevation after intravitreal injections